Portal Vein Thrombosis Repeatedly Observed in a Cirrhotic Patient with Antiphospholipid Antibody Syndrome - Ohe, Mari; Mutsuki, Taishi; Goya, Takeshi; Yamashita, Shinsaku; Satoh, Takeaki; Kohjima, Motoyuki; Kato, Masaki (Fukuoka igaku zasshi = Hukuoka acta medica, 2016)
Although portal vein thrombosis in cirrhotic patients is frequently observed, the detailed process remains to be clarified, and the role of anticardiolipin antibody in the development of portal vein thrombosis has been controversial. A 52-year-old man, who had been diagnosed with alcoholic cirrhosis of the liver, was admitted to our hospital suffering from dyspnea and ascites. Just after being diagnosed as having antiphospholipid antibody syndrome with lung thrombosis and delivering a positive result for the β 2-glycoprotein I-dependent anticardiolipin antibody, he sustained rupture of the esophageal varices with rapid development of portal vein thrombosis, which resolved under anticoagulant therapy. Two years later, he was admitted again on suspicion of thrombosis because of an elevation in the serum D-dimer level, and computed tomography showed portal and upper mesenteric vein thrombosis. Although immediate anticoagulant therapy resulted in complete recanalization, he suffered the same episode 2 months later, which occurred with re-elevation of the serum D-dimer level. A positive finding of an anticardiolipin antibody in cirrhotic patients has been considered to be nonspecific and not related to the development of thrombus in the portal vein. This case, however, seems to indicate that cirrhotic patients with the β2-glycoprotein I-dependent anticardiolipin antibody should be regarded as being at high risk for portal vein thrombosis. Monitoring with the serum D-dimer was useful in detecting portal vein thrombosis in its early stage.